7.9k views
1 vote
Solve the following equations
a) 2(x - 1) = 4 (x + 2)
b)(3 - x) (x + 2) = 0


User AlBaraa Sh
by
5.6k points

1 Answer

5 votes

Answer:

see below

Explanation:

a) 2(x - 1) = 4 (x + 2)

Distribute

2x-2 = 4x+8

Subtract 2x from each side

2x-2x-2 = 4x-2x +8

-2 = 2x+8

Subtract 8 from each side

-2-8 = 2x+8-8

-10=2x

Divide each side by 2

-10/2 = 2x/2

-5 =x

b)(3 - x) (x + 2) = 0

We can use the zero product property

3-x = 0 x+2= 0

3-x+x=0+x x+2-2=0-2

3=x x=-2

User Derjanb
by
6.3k points